Politik Hilirisasi Desa dan Aksesibilitas Keuangan Mikro Syariah dalam Produksi Bandeng Junok Sreseh Sampang - Nurul Aulia; Mashudi Mashudi; Dahruji Dahruji (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2025)
The milkfish pindang business in Junok Village, Sreseh District, Sampang Regency, is one of the leading businesses that is in great demand by the local community. However, this business has not developed optimally and is still limited to this area. For this reason, efforts are needed to optimize village downstreaming and access to sharia microfinance to support pindang milkfish production so that it can develop more widely and provide a greater economic impact for the community. This research aims to analyze the role of village government in optimizing these two things, as well as contributing to sustainable local economic development. The research method used is qualitative, with data collection techniques through in-depth interviews and observation. The research results show that the Junok village government has made various efforts to optimize village downstreaming, including training in milkfish cultivation, setting harvest schedules, and also plans to facilitate financing from sharia microfinance institutions (LKMS). Even though there are several obstacles, such as a lack of financial knowledge among farmers and limited equipment, the village government continues to try to overcome this problem through assistance and education. Overall, the efforts made are quite optimal and have the potential to support the development of the milkfish pindang business in the future.